Об автохтонном происхождении слова alkà - Sausverde, Erika (Baltistica, 1989)
CONCERNING THE AUTOCHTONIC ORIGIN OF LITH. ALKÀ The word alkà exists only in the Baltic and Germanic languages and has no cognates in the other Indo-European branches. So the autochtonic nature of alkà has been suggested. The origin of this word may be related with the neolithic cultures of Narva and Ertebölle, which have much in common and often are related to each other.